Islamic Bioethics: The Art of Decision Making - Ali Akhmad, Syaefudin; Rosita, Linda (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 2 (2012): Indonesian Journal of Legal and Forensic Sciences)
In Islam, bioethical decision-making is carried out within a framework of values derived from the revelation andtradition. Islamic bioethics or Islamic medical ethics are referring to Islamic guidance on ethics and moral issuesrelated to medical and scientific fields, especially those dealing with human, based from the Quran and Hadith.In Islam, human is one of the most sacred creatures of God. Therefore, he/she must be appreciated, respected andwell protected. Apparently, Muslim doctors have always been facing dilemmas on bioethical decision makingduring their practices. There are so many conflicting issues coming from multiple points of views such asdiscipline, legal, ethical, sharia, social, cultural and financial aspects. Muslim doctors should answer thedilemmas on each diagnosis and treatment intervention by having a good decision making as their first step. Byimplementing Islamic framework on bioethical decision making, guided by sharia which includes Quran,Hadith, Ijma, and Qiyas, it is expected that this framework will be able to assist Moslem doctors to solve theirdilemmas in this world and in the hereafter. A triangulation framework known as islamic bioethics consisting oftriangle I and triangle II will ease Moslem doctors to have the final decision for their daily medical practices.These triangle framework will be powerfull in use if combined with Prima Facie approach and a five-digitapproach.
Keywords: Islamic Bioethics, maqosidus-syariah, qowaidus-syariah, triangle framework, bioethical decision making